Effect of n-hexane extract of Tinospora crispa on reduced glutathione and malondialdehyde level in paracetamol induced hepatotoxicity in rats - Emon Rashid; Zesmin Fauzia Dewan (Update Dental College, 2018)
The present study demonstrates that, treatment with the nhexane extract of Tinospora crispa was able to ameliorate chronic hepatotoxicity due to oxidative stress e.g. Paracetamol induced hepatotoxicity. Considering the biochemical and histological parameters together, it was observed that hepatic reduced glutathione (GSH) concentrations of the n-hexane extract post treated group was increased to significant level and hepatic malondialdehyde (MDA) concentration was reduced to significantly lower level compared to the paracetamol treated groups. This study suggests near normal alleviation of paracetamol induced chronic hepatotoxicity in rats. Update Dent. Coll. j: 2018; 8 (2): 5-9